The Efficiency of Water Tube Boiler Performance Using Direct Method on the Utility Unit - Mulyani*, Yully; Dhamayanthie, Indah; Hilmi, Muhammad Irfan (Universitas Syiah Kuala, 2023)
Boiler efficiency is a quantity that shows the relationship between the incoming energy supply into the boiler and the output energy produced by the boiler. The goal is to calculate the performance efficiency of the water tube boiler. Factors that affect the decrease in the efficiency of water tube boilers, namely the production of steam produced, the amount of fuel used, excess water, burner, flue gas temperature, fouling, blowdown, boiler feed water temperature, and the effect of fuel. Based on data and analysis of the direct method, the highest efficiency of the water tube boiler, namely on July 26, 2022, was 90.77%, producing 80,000 kg/hour of steam, while the lowest efficiency of the water tube boiler, namely on July 23, 2022, was 46.03%, due to the use fuel is very high, which is around 4011 kg/hour and only produces steam as much as 55000 kg/hour.